Ocena stopnia zanieczyszczenia gleb na pograniczu byłej strefy ochronnej Huty Miedzi "Głogów" = Assessment of soils? pollution level on peripheries of the former protective zone of the Copper Smelter "Głogów" - Przewocka, Marta; Rosada, Janusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The environmental friendly activities carried on for many years by the Copper Smelter GŁOGÓW contributed to a significant reduction of the majority of negative effects of factory?s influence on the environment. A modernization of the copper production technology and introduction of effective purification systems led to a substantial improvement of the agrocenoses surrounding the Smelter.
Keywords: metale ciężkie; Huta Miedzi "Głogów"; środowisko; gleba; heavy metals; Copper Smelter Głogów; soils; environment